Pengaruh Influencer Marketing dan Content Marketing Terhadap Brand Awareness Produk Avoskin: (Studi pada Instagram @avoskinbeauty) - Muzakki, Farah Daroin Putri; Andarini, Sonja (Universitas Sam Ratulangi, 2024)
This research aims to identify and determine the Influence of Influencer Marketing and Content Marketing on Brand Awareness of Avoskin Products (Study on Instagram @avoskinbeauty). The research method is quantitative, using a questionnaire distributed to 130 respondents. The research population consisted of Instagram followers @avoskinbeauty and known influencer Refal Hady, selected through purposive sampling. The data analysis method used is multiple linear regression. The results of this research are as follows: 1) Simultaneously Influencer Marketing and Content Marketing have a significant effect on Brand Awareness Avoskin products by involving Instagram @avoskinbeauty, 2) Partially Influencer Marketing has a significant effect on Brand Awareness Avoskin products by involving Instagram @avoskinbeauty, 3) Partially Content Marketing has a significant effect on Brand Awareness Avoskin products by involving Instagram @avoskinbeauty.